DETERMINING CRITICAL WEED COMPETITION PERIODS FOR BLACK SEED - M. A. Nadeem; A. Tanveer; T. Naqqash; A. J. Jhala; K. Mubeen (Journal of Animal and Plant Sciences, 2013)
Effect of weed competition periods on weeds and yield of black seed was studied through field experiments conducted at Agronomic Research Area, University of Agriculture, Faisalabad during winter 2006-07 and 2007-08. Weeds were allowed to compete with the crop for 40, 50, 60, 70, 80 days after sowing and throughout the growth season along with a weed free treatment. The data on weed density and biomass; yield components and yield of black seed were documented. Weed density and biomass increased with the increase in weed competition periods and the maximum weed density and biomass was recorded in weedy check during both the years of study. Outcome of the differences between the weed free and competition for 40 days after emergence was statistically similar for number of capsules per plant, number of branches and number of seeds per capsule during first year of study, however, all yield components showed a significant decline when weeds were allowed to compete compared with weed free treatments during second year. The maximumseed yield was recorded in weed free treatment and it showed a linear decline as the weed competition period was increased during both the years of study. Weeds must be controlled within 40 days after emergence of black seed to avoid the risk of economic yield loss as it has been found to be the critical period of weed crop competition in black seed.
Keywords: Black seed; Weed-crop competition; Weeds; Yield; Pakistan